Gender Differences in Private and Public Goal Setting - Jordi Brandts; Sabrine El Baroudi; Stefanie Huber; Christina Rott (Tinbergen Institute, 2022)
We conduct a field and an online classroom experiment to study gender differences in self-set performance goals and their effects on performance in a real-effort task. We distinguish between public and private goals, performance being public and identifiable in both cases. Participants set significantly more ambitious goals when these are public. Women choose lower goals than men in both treatments. Men perform better than women under private and public goals as well as in the absence of goal setting, consistent with the identifiability of performance causing gender differences, as found in other studies. Compared to private goal setting, public goal setting does not affect men's performance at all but it leads to women's performance being significantly lower. Comparing self-set goals with actual performance we find that under private goal setting women's performance is on average 67% of goals, whereas for men it is 57%. Under public goal setting the corresponding percentages are 43% and 39%, respectively.
Keywords: C91; J01; J16; J82; 330; gender differences; goal setting; public observability; experiment